The feeding habits of the Southern elephant seal, Mirounga leonina, at Isla 25 de Mayo/King George Island, South Shetland Islands - Daneri, Gustavo Adolfo; Carlini, A.R.; Marschoff, Enrique Ricardo; Harrington, Ana; Negrete, Javier; Mennucci, J.A.; Márquez, M. E. I. (Polar Biology)
The Southern elephant seal (Mirounga leonina) is a major consumer from the Southern Ocean. This species is highly sexually dimorphic and frequently exhibits resource partitioning according to sex and/or age classes. This study analysed the feeding habits of the M. leonina population from Isla 25 de mayo (King George Island) in the spring/summer seasons of 1995/1996–2002/2003. A total of 232 individuals from different sex-age groups were stomach lavaged. The analysis of stomach samples showed that cephalopods were the main prey followed by fish, their frequency of occurrence being 98.1 and 17.9 % respectively. Cephalopods were dominated by the Antarctic glacial squid, Psychroteuthis glacialis, which occurred in 83 % of samples, constituting 57.2 % in numbers and 61.3 % in mass. Octopods were of lesser relevance, occurring in 18 % of samples, but became more important in the diet of male individuals. Juvenile seals fed on a lower variety of cephalopod prey than older ones. This would coincide with the diving pattern characteristic of the different sex-age categories of seals. The predominance of P. glacialis might be associated with the more southerly location of the foraging areas of this population compared to others. Fish were largely represented by the myctophid Gymnoscopelus nicholsi, which occurred in 81.3 % of samples containing otoliths and constituted 76.4 % in numbers and 66.4 % in mass. However, while myctophids may be the dominant fish prey of elephant seals in areas close to the South Shetlands, they would be probably replaced by P. antarcticum as seals migrate towards higher latitudes. Fil: Daneri, Gustavo Adolfo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Carlini, A.R. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto ...